(untitled) - Asian Development Bank (Ha Noi, 2004)
The new concept of Base of the Pyramid (BOP) shows that poor people can be integrated with markets in ways that enable them to access goods and services of high quality and also to become suppliers of good quality and reliable inputs. This bulletin examines the BOP concept, and gives some examples that are already being applied in Vietnam, in addition to discussing potential ways of increasing the effectiveness of selling to, and buying from, the Base of the Pyramid
Keywords: Market segmentations,Market segmentations